Engaging Imagination : Helping Students Become Creative and Reflective Thinkers. - James, Alison (Wiley, 2014)
How to nurture creativity in tomorrow's innovators-today's college students When asked what they want colleges to emphasize most, employers didn't put science, computing, math, or business management first. According to AAC & U's 2013 employer survey, 95% of employers give hiring preference to college graduates with skills that will enable them to contribute to innovation in the workplace. In Engaging Imagination: Helping Students Become Creative and Reflective Thinkers, two leading educators help college instructors across disciplines engage students in nurturing creat.